Quantitative Flow Analysis Around Aquatic Animals Using Laser Sheet Particle Image Velocimetry - Stamhuis, Eize J.; Videler, John J. (Journal of experimental biology, 1995)
Two alternative particle image velocimetry (PIV) methods have been developed, applying laser light sheet illumination of particle-seeded flows around marine organisms. Successive video images, recorded perpendicular to a light sheet parallel to the main stream, were digitized and processed to map the flow velocity in two-dimensional planes. In particle tracking velocimetry (PTV), displacements of single particles in two subsequent images were determined semi-automatically, resulting in flow diagrams consisting of non-uniformly distributed velocity vectors. Application of grid-cell averaging resulted in flow field diagrams with uniform vector distribution. In sub-image correlation PIV (SCPIV), repetitive convolution filtering of small sub-areas of two subsequent images resulted in automatic determination of cross-correlation peaks, yielding flow field diagrams with regularly spaced velocity vectors. In both PTV and SCPIV, missing values, caused by incomplete particle displacement information in some areas of the images or due to rejection of some erroneous vectors by the vector validation procedure, were interpolated using a two-dimensional spline interpolation technique. The resultant vector flow fields were used to study the spatial distribution of velocity, spatial acceleration, vorticity, strain and shear. These flow fields could also be used to test for flow in the third dimension by studying the divergence, and to detect the presence and location of vortices. The results offer detailed quantitative descriptions of the flow morphology and can be used to assess dissipated energy. The versatile character of the technique makes it applicable to a wide range of fluid mechanical subjects within biological research. So far it has been successfully applied to map the flow around swimming copepods, fish larvae and juvenile fish and the ventilation current of a tube-living shrimp.